The SIOP Model Implementation in EFL Teachers Online Literacy Coaching Program - Ayudaniska Mutmainnah; Ilza Mayuni; Darmahusni (ICHELSS: International Conference on Humanities, Education, Law, and Social Sciences, 2021)
Abstract: Promoting teachers’ professional development is crucial as they are expected to plan, implement, and solve practical problems in the learning process. However, teachers responsible for educating their learners are not always provided with sufficient professional development, especially during this Covid-19 outbreak. This study focused on implementing Sheltered Instruction Observation Protocol (SIOP), a teaching model that allows teachers to improve the English skills of learners by using specific techniques and engage them in a comprehensible manner. The purpose is to provide an overview of how the SIOP model is implemented by EFL teachers based on its components and features. The participants, 31 English teachers from all around Indonesia, are selected based on their experiences as English instructors. Within two cycles of online literacy coaching, their lesson plan, teaching practice, and self-reflection during the program are observed using mixed methods. The researcher used field notes, SIOP observation protocol, and forum group discussion to collecting the data. The results indicate that the SIOP implementation score increased by 5 points from 83% at the first cycle become 88% at the second cycle. It means that, on average, the participants gained a high level of SIOP implementation. Based on the reflective session result, 87% of the participants implemented all the SIOP features, where strategies and review & assessment are the features that they mostly overlook. Then, it is suggested to conduct further studies of the SIOP model on another context of professional development by ensuring that all participants are provided with resources that support the learning process. Keywords: English Teacher, Literacy Learning, Online Literacy Coaching, Siop Model, Professional Development